The Impact of Tax Reform, Subjective Norms and Social Norms on SME’s Tax Compliance during the Covid-19 Pandemic - Agustine Dwianika; Putri Dwi Wahyuni; Fachrul Roza (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2023)
This study aims to determine the direction of tax reform, subjective norms and during social norms on SME tax obligations of  SMEs in DKI Jakarta Region during Pandemic Covid-19 collected by  questionnaires. Result shows partial taxation reforms and social norms have a positive impact on SME tax obligations, but  subjective norms are not related to SME tax obligations. In addition, tax reform , subjective norms, and simultaneous social norms are positive for taxpayer compliance. This finding would be useful for DGT for brainstorming references of SME’s policy and  tax strategy.